(untitled) (Annals of Medical Research, 2021)
Aim: We aimed to investigate the incidence of latent tuberculosis infection (LTBI) and seroconversion rate of LTBI screening tests under anti-TNF-α treatment, in our pediatric patients with chronic rheumatic diseases.Material and Methods: The data of 47 patients received anti-TNF-α treatment for different chronic rheumatic diseases between May-2015 and May-2018, were reviewed retrospectively. Demographics and clinical findings of the patients, as well as the treatments and their durations, were collected. The tuberculin skin test (TST) and Quantiferon-TB-Gold in-tube (QFT) test results at initiation and one year after the anti-TNF-α treatment were compared. Results: The study group included 38 (80.8%) patients with juvenile idiopathic arthritis, six (12.7%) with idiopathic uveitis, two (4.2%) with Behçet’s disease related uveitis and one (2.1%) with juvenile dermatomyositis. For a period at least one year, 33 (70.2%) patients received etanercept, 12 (25.5%) received infliximab and two (4.2%) received adalimumab treatment. Before anti-TNF-α treatment, 31.9% of the patients were diagnosed with LTBI. After one year of treatment, it was found to be increased to 44.6%. During treatment, the seroconversion rate of the screening tests for LTBI was determined to be 12.7% (6/47).Conclusion: The seroconversion rate of screening tests for LTBI was found high in pediatric patients receiving anti-TNF-α treatment. Although the consistency between TST and QFT tests was found weak in our study, the fact that these tests should be used and evaluated together in the follow-up in the light of current guidelines in terms of LTBI and active tuberculosis development, remains still up to date. Further research is need in order for more enlightening data on the risk of LTBI and active tuberculosis in patients under anti-TNF-α treatment.